Bacillus thuringiensis delta-endotoxin binding to brush border membrane vesicles of rice stem borers - Alcantara, Edwin P.; Aguda, Remedios M.; Curtiss, April; Dean, Donald H.; Cohen, Michael B. (Wiley, 2004)
The receptor binding step in the molecular mode of action of five δ‐endotoxins (Cry1Ab, Cry1Ac, Cry1C, Cry2A, and Cry9C) from Bacillus thuringiensis was examined to find toxins with different receptor sites in the midgut of the striped stem borer (SSB) Chilo suppressalis (Walker) and yellow stem borer (YSB) Scirpophaga incertulas (Walker) (Lepidoptera: Pyralidae). Homologous competition assays were used to estimate binding affinities (Kcom) of 125I‐labelled toxins to brush border membrane vesicles (BBMV). The SSB BBMV affinities in decreasing order was: Cry1Ab = Cry1Ac > Cry9C > Cry2A > Cry1C. In YSB, the order of decreasing affinities was: Cry1Ac > Cry1Ab > Cry9C = Cry2A > Cry1C. The number of binding sites (Bmax) estimated by homologous competition binding among the Cry toxins did not affect toxin binding affinity (Kcom) to both insect midgut BBMVs. Results of the heterologous competition binding assays suggest that Cry1Ab and Cry1Ac compete for the same binding sites in SSB and YSB. Other toxins bind with weak (Cry1C, Cry2A) or no affinity (Cry9C) to Cry1Ab and Cry1Ac binding sites in both species. Cry2A had the lowest toxicity to 10‐day‐old SSB and Cry1Ab and Cry1Ac were the most toxic. Taken together, the results of this study show that Cry1Ab or Cry1Ac could be combined with either Cry1C, Cry2A, or Cry9C for more durable resistance in transgenic rice. Cry1Ab should not be used together with Cry1Ac because a mutation in one receptor site could diminish binding of both toxins. Arch. Insect Biochem. Physiol. 55:169–177, 2004. © 2004 Wiley‐Liss, Inc.